Investigations on Charge Transport Mechanisms in Mixed Valent La0.5Pr0.2Ba0.3–xCaxMnO3 Manganites. (2018) - Boricha, Hetal; Rajyaguru, Bhargav; Joshi, Zalak; Markna, J.H.; Pandya, D.D.; Joshi, A.D.; Solanki, P.S.; Shah, N.A.
Abstract: In this communication, we report the results of the studies on the structural and transport properties of La0.5 Pr0.2 Ba0.3–x Cax MnO3 (LPBCMO; x = 0.00, 0.05, 0.15, 0.20 & 0.25) manganites, synthesized by conventional solid state reaction route. All the samples possess distorted orthorhombic structure verified by Rietveld refinements. Temperature dependent resistance of LPBCMO samples shows an exhibition of metal to insulator (semiconductor) phase transition at temperature TP . To understand the charge transport mechanisms responsible for these two electronic phases, zener double exchange (ZDE) polynomial law and Mott type variable range hopping (VRH) model have been used for metallic and semiconducting regions, respectively. Possible nature of the charge carrier interactions with the lattice and activation energy have been discussed on the basis of these theoretical fittings to the resistance data.